2022
DOI: 10.3390/cancers15010122
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Local Recurrence after Intraoperative Microwave Ablation for Colorectal Liver Metastases

Abstract: This study aimed to clarify local recurrence (LR) predictive factors following intraoperative microwave ablation (MWA) for colorectal liver metastases. The data from 195 patients with 1392 CRLM lesions, who were preoperatively diagnosed by gadolinium-enhanced MRI with diffusion-weighted imaging and dynamic CT and treated with intraoperative MWA (2450 MHz) with or without hepatectomy, from January 2005 to December 2019, were retrospectively reviewed and analyzed using logistic regression. In addition, the margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Tumor size and ablation margin—frequently determined by cross-sectional imaging obtained a few weeks after the procedure—have been identified as significant factors in incomplete ablation and local recurrence, which historically has been reported to be as low as 4% with MWA. 35 36 Retrospective analyses and meta-analyses have regularly evaluated this clinical question. One recent meta-analyses of 740 patients from 10 retrospective studies of ablation in HCC demonstrated significantly lower tumor recurrence rates and greater 5-year disease-free survival in the surgical ablation group despite larger tumor sizes in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor size and ablation margin—frequently determined by cross-sectional imaging obtained a few weeks after the procedure—have been identified as significant factors in incomplete ablation and local recurrence, which historically has been reported to be as low as 4% with MWA. 35 36 Retrospective analyses and meta-analyses have regularly evaluated this clinical question. One recent meta-analyses of 740 patients from 10 retrospective studies of ablation in HCC demonstrated significantly lower tumor recurrence rates and greater 5-year disease-free survival in the surgical ablation group despite larger tumor sizes in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing tumor size is often cited as a risk factor for recurrence, although the ablation zone margin may be a better measure of recurrence risk instead of initial tumor size. 25,35…”
Section: Locationmentioning
confidence: 99%
“…For CLM, it has been shown that minimum ablation margins of at least 5 mm and ideally 10 mm are critical for prolonged local tumour progression-free survival, regardless of the thermal ablation modality used (RFA or MWA). 5,[12][13][14][15]17,18,[55][56][57][58] This is referred to as an A0 ablation, analogous to surgical resections with clear microscopic margins (R0) and is essential to provide local cure and serve as a surgical alternative, since the majority of intrahepatic micrometastases are within 1 cm of the gross tumour. 59 When a 10 mm minimal margin can be achieved, local tumour progression free-survival exceeds 95% and can offer a chance for local cure similar to surgery, without the associated morbidity.…”
Section: Ablation Marginsmentioning
confidence: 99%
“…Multiple studies have proven that the most important technical factor for local tumour control is ablation with adequate margins. For CLM, it has been shown that minimum ablation margins of at least 5 mm and ideally 10 mm are critical for prolonged local tumour progression‐free survival, regardless of the thermal ablation modality used (RFA or MWA) 5,12–15,17,18,55–58 . This is referred to as an A0 ablation , analogous to surgical resections with clear microscopic margins (R0) and is essential to provide local cure and serve as a surgical alternative, since the majority of intrahepatic micrometastases are within 1 cm of the gross tumour 59 .…”
Section: Ablation Marginsmentioning
confidence: 99%
“…Prior work studied factors that are statistically significant for prediction of LTP after an ablation treatment, mostly focused on liver ablation procedures. These factors include minimal ablation margins, volume of insufficient coverage (unablated tumor volume), tumor size, tumor number, tumor subtype (e.g., adenocarcinoma and squamous cell carcinoma), adjoining with blood vessels of diameter >= 3 mm, and tumor location [1], [2], [3], [4], [5], [6]. Staal et al also applied multiple statistical radiomics (e.g., HU uniformity, mean, and kurtosis) of both ablation zone and peri-ablation zone to predict LTP for colorectal liver metastases in the liver [3].…”
Section: Introductionmentioning
confidence: 99%